Twerking and Cultural Appropriation: Miley Cyrus' Display of Racial Ignorance - Zink, Shereen (MacEwan University Student eJournal, 2016)
Miley Cyrus’ recent habit of twerking has sparked debate over whether the pop star is misappropriating African American culture; some even going so far as to accuse her of racism. This paper reviews the literature that exists in the public sphere on the topic, and delves into a scholarly analysis of Cyrus’ actions, statements, and the implications they have. My own post-analysis interpretation of the issue is addressed in the concluding paragraphs. Ultimately, twerking’s political context, and Cyrus’ lack of regard for said context, suggest that she is perpetuating harmful stereotypes about black women while her own white privilege allows her to maintain her integrity. Cyrus may not be intentionally exploiting black culture, but she is certainly communicating more than she may have bargained for.